Congenital hyperinsulinism in the Ukraine: a 10-year national study - Globa, Evgenia; Christesen, Henrik Thybo; Mortensen, Michael Bau; Houghton, Jayne A. L.; Nielsen, Anne Lerberg; Detlefsen, Sönke; Flanagan, Sarah E. (Frontiers in Endocrinology, 2024)
Introduction Congenital Hyperinsulinism (CHI) has not been previously studied in Ukraine. We therefore aimed to elucidate the genetics, clinical phenotype, histological subtype, treatment and long-term outcomes of Ukrainian patients with CHI. Methods Forty-one patients with CHI were recruited to the Ukrainian national registry between the years 2014-2023. Genetic testing (n=40), 18F-fluorodihydroxyphenylalanin and 68Ga-DOTANOC PET/CT imaging followed by surgical treatment and subsequent histological analysis (n=19) was performed through international collaboration. Results Pathogenic variants were identified in 19/22 (86.3%) individuals with persistent CHI (p-CHI) and 8/18 (44.4%) with early remission CHI (er-CHI). Pathogenic variants in the K-ATP channel genes were the only identified genetic cause of p-CHI (ABCC8 (n=17) and KCNJ11 (n=2)) with greater genetic heterogeneity observed in those with er-CHI (ABCC8 (n=3), KMT2D (Kabuki Syndrome, n=1), Beckwith-Wiedemann syndrome (n=2) and INSR (Donohue syndrome (n=2)). Histological analysis performed on 19 children with persistent CHI confirmed focal disease in 14 (73.7%), diffuse disease in two (10.5%) and atypical histology in three (15.8%). After surgery, complete recovery was observed in all 14 with focal disease, while relapse occurred in three patients with diffuse or atypical histology. Conclusion A genetic diagnosis was achieved for 67.5% (27/40) of the cohort with a higher pick-up rate observed in those with p-CHI. The genetics and imaging studies enabled subtype-targeted treatment with surgical cure achieved in all individuals with focal disease.